Estudio de prefactibilidad para la instalación de un hostel backpacker que utiliza la metodología “empleo con apoyo” para emplear a personas con Síndrome de Down en Cusco - Herrada García, Ingrid Margarita (2020)
With the following preliminary study, it is aimed to determine the technical, economic and financial viability of the installation of a hostel backpacker in Cusco that promotes labor insertion for people with Down syndrome. The service offered is addressed to people between 24 and 35 years old who like adventurous and cultural activities. Tourism is expanding globally, as well as in Peru, a country with wonderful tourist’s attractions that impacts in the creation of more jobs. However, according to the National Institute of Statistics and Computing the level of unemployment in Peru remains of an average of 6% (Instituto Nacional de Estadística e Informática [INEI], 2019). Moreover, the unemployment rate of people with an intellectual disability reached 16.6% (Macera, 2018). In this way, not only does this preliminary study seeks to prove this is a profitable business but seeks to generate more jobs for the population with disabilities. The service will be offered online or clients may take it in person. Thanks to the methodology “Employment with Support”, the hostel with provide an integral accompaniment throughout the employees work experience. On the other hand, the demand of the project is 18,000 people for 2021 with a purchase intention of 99%. Moreover, the property where the hotel will be implemented, in Cusco, belongs to one of the shareholders of the project, has an area of 500 square meters and will be modified for the installation of the hostel. Likewise, technology will determine the capacity of the project, which could only serve quantity of 12,775 people per year, being the main limiting the capacity of the building of 50 beds. Further, it is estimated that the project implementation will take 350 days. Finally, the total investment required of the project is S/. 451,666 with 40% of financing. It has been demonstrated that the project is financially profitable with an IRR of 45% and a NPV of S /.526,508.42. With a recovery period of approximately 2 years.